Bagongan and Babasan Language in Javanese Indramayu Dialect: Sociolinguistics Approach - Sry Satriya Tjatur Wisnu Sasangka; Dewi Nastiti Lestariningsih; Anis Rahmawati; Saefu Zaman; Mukhamdanah; Nurweni Saptawuryandari; Sutejo Sutejo (Cogent Arts & Humanities)
Most of the residents of Indramayu, West Java use the Javanese dialect of Indramayu. When viewed from its form, the Indramayu dialect is simpler than standard Javanese because it only recognizes two variants, namely bagongan and bebasan, both at the lexicon and structure level. Both variants are equivalent to ngoko (rough) and krama (smooth) in standard Javanese. Bagongan is used in informal situations, while bebasan is in formal situations. This study aims to describe the variety of bagongan and bebasan, both at the lexicon and structure level so that the peculiarities of the dialect can be adequately revealed. For this reason, a qualitative approach is used by utilizing descriptive, comparative, and inferential methods. The results show that in the Indramayu dialect, most of the bagongan and bebasan lexicons can be used by the first, second, and/or third personas interchangeably. In addition, most of the bebasan lexicons do not have a subtle variant and are very smooth. The lexicon of the bagongan cannot appear in a bebasan structure; The bebasan lexicon also cannot appear in the bagongan structure.